Preventing MRSA Infections in Sports: Effective Strategies and Approaches - Karolina Pawłuszkiewicz; Natalia Kucharczyk; Emilia Kucharczyk (Quality in Sport)
Introduction: Infections caused by community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) are a growing concern, particularly among asymptomatic individuals. CA-MRSA can lead to various conditions such as skin infections, septic arthritis, pyomyositis, endocarditis, and pubic osteomyelitis, with athletes being especially vulnerable due to shared equipment, close contact, and skin trauma. Prolonged colonization of the anterior nares and persistence on shared surfaces contribute to its spread.